Influence of polyphenols on sensory properties of fermented sausages. Issue 1 (October 2021) - Nikolic, A; Grkovic, N; Djuric, S; Jovanovic, J; Djordjevic, V; Trbovic, D; Vasilev, D
Abstract: In the current research, the use of polyphenols in the production of fermented sausages as a natural preservative and their influence on the sensory characteristics of these products were investigated. Polyphenols could have antimicrobial and antioxidant roles in meat products, but also a range of positive biological effects on consumers. The results of the research showed that the addition of polyphenols did not significantly affect the sensory properties (colour, cross-section appearance, consistency, odour and flavour) of the three groups of sausages (control fermented sausage and two sausage variants, one with nitrite and one without nitrite), and that sausages were highly rated during most of the storage period. In addition, all tested sausages were evaluated as acceptable until the end of the entire storage period, i.e., throughout the 280-day period after sausage production.